2021
DOI: 10.1039/d1nr04583k
|View full text |Cite
|
Sign up to set email alerts
|

One-way rotation of a chemically anchored single molecule-rotor

Abstract: Superimposed STM images of the six stable rotation stations of a DMBI-P molecule during a step by step clockwise rotation induced by voltage pulses (V = 0.5 V, I = 0.5 nA, t = 10 s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
(39 reference statements)
2
19
0
Order By: Relevance
“…30,31 It was, however, soon observed that decomposition reactions occur during the doping process, with the halide separation or the splitting of a methyl group. 32 When sublimating o-OMe-DMBI-I in ultrahigh vacuum (UHV), the molecule undergoes a dissociation reaction where the methoxy group is cleaved and methyl iodide is released, yielding the zwitterionic phenolate DMBI-P. 11 In a recent study, we showed that on Au(111) DMBI-P works as a single-molecule rotor reliably converting STM voltage pulses into controllable unidirectional rotation. 11 Here, we investigated the zwitterionic phenolate to make the methoxy cleavage superfluous and elongated the rotating part to a naphthyl, obtaining A representative overview STM image (Figure 1b) shows a moderate coverage of about 0.1 ML.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…30,31 It was, however, soon observed that decomposition reactions occur during the doping process, with the halide separation or the splitting of a methyl group. 32 When sublimating o-OMe-DMBI-I in ultrahigh vacuum (UHV), the molecule undergoes a dissociation reaction where the methoxy group is cleaved and methyl iodide is released, yielding the zwitterionic phenolate DMBI-P. 11 In a recent study, we showed that on Au(111) DMBI-P works as a single-molecule rotor reliably converting STM voltage pulses into controllable unidirectional rotation. 11 Here, we investigated the zwitterionic phenolate to make the methoxy cleavage superfluous and elongated the rotating part to a naphthyl, obtaining A representative overview STM image (Figure 1b) shows a moderate coverage of about 0.1 ML.…”
Section: Resultsmentioning
confidence: 99%
“…At voltages higher than 400 mV, the yield for rotation and translation are very similar, and a nearly constant yield of about 5 × 10 −10 events/electron is observed in both cases. For rotations, a threshold voltage at about 400 mV is visible in the upper plot, which can be explained by the onset of the C−H stretch mode of the methyl group at the opposite side of the Au−O bond, in agreement with the case of the shorter DMBI-P. 11 Fitting the experimental action spectra by the theory of ref 34 (continuous lines in the upper panel of Figure 6), we obtain a threshold at 370 meV (see Methods for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning probe microscopy with its high spatial resolution and the ability of single-molecule manipulation is an ideal technique to accomplish this task. For more than three decades, single-atomic and molecular switches have been observed by means of SPM, revealing rotations, tautomerizations, and various kinds of bistable configurations. However, such switching usually consist of one process only, e.g., tautomerization or rotation, and the specific stimuli can individually be identified. For example, the C–H and the CC stretch mode have been shown to excite the rotation of cis -2-butene on the surface of palladium. , In contrast, the excitation of one vibrational mode, which then triggers more than one process hasto the best of our knowledgenot yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology enables us to observe structures and analyse phenomena at the atomic and molecular sizes (so called the nanoscale). 8 Mainly based on developments of high-resolution microscopies 9 and related analytical tools, 10 one can consider the advocacy of the concept of nanotechnology to have stimulated research at the nanoscale. Promoted understanding of nanoscale materials has enabled the construction of functional materials with new insights.…”
Section: Introductionmentioning
confidence: 99%